Perancancangan dan Simulasi Sistem Informasi Akademik Berbasis Wireless Application Protocol (WAP) - Dwirgo Sahlinal; Kurniawan Saputra; Mochammad Yusman (Politeknik Negeri Lampung, 2008)
The Application Academic Information System based WAP is very needed in order to implement Information Technology into Teaching-Learning Process in University. By Using Emulator WAP as aid-equipment for simulating Academic Information System, will result an optimum output in developing Information System based WAP. Handphone as telecommunication equipment which is completed by WAP-GPRS facility can be used as an access Academic Information System through internet. Â Kata Kunci : WAP, Sistem Informasi Akademik, emulator, GPRS